2003
DOI: 10.1051/0004-6361:20031343
|View full text |Cite
|
Sign up to set email alerts
|

Chandradiscovery of an X-ray jet and lobes in 3C 15

Abstract: Abstract.We report the Chandra detection of an X-ray jet in 3C 15. The peak of the X-ray emission in the jet is 4.1 (a projected distance of 5.1 kpc) from the nucleus, and coincident with a component previously identified in the radio and optical jets. We construct the spectral energy distribution (SED) for this component, optical knot C, and find that X-ray flux is well below the extrapolation of the radio-to-optical continuum. We examine four models for the X-ray jet emission: (I) weak synchrotron cooling in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
6
39
0
Order By: Relevance
“…For this conservative estimate we used a spectral index which is quite flat for a jet. In fact, the radio-optical spectral index of the X-ray brightest jet knot ("Knot C"; Kataoka et al 2003) is argued to be steeper than our chosen value (Kataoka et al 2003;Dulwich et al 2007). …”
Section: Notesmentioning
confidence: 70%
“…For this conservative estimate we used a spectral index which is quite flat for a jet. In fact, the radio-optical spectral index of the X-ray brightest jet knot ("Knot C"; Kataoka et al 2003) is argued to be steeper than our chosen value (Kataoka et al 2003;Dulwich et al 2007). …”
Section: Notesmentioning
confidence: 70%
“…Our study is stimulated by recent results from the Chandra X-Ray Observatory, which have shown that X-ray jet emission is common in FR I sources (Hardcastle et al , 2005Harris et al 2002aHarris et al , 2002bKataoka et al 2003;Kraft et al 2002;Marshall et al 2002;Wilson & Yang 2002;Worrall et al 2001Worrall et al , 2003. The established synchrotron origin of this X-ray emission (see all the references above) 2 implies that the kiloparsec-scale jets in FR I radio galaxies will, at some level, be sources of high-and very high energy -ray emission due to the inverse-Compton scattering of ambient (galactic) photon fields by the synchrotron-emitting electrons.…”
Section: Introductionmentioning
confidence: 90%
“…The Chandra X-Ray Observatory and XMM-Newton have allowed a number of detections of X-ray emission from lobes to be made. In many sources the lobes have been claimed to be near to equipartition (e.g., Hardcastle et al 2002;Belsole et al 2004;Croston et al 2004;Bondi et al 2004;Overzier et al 2005), whereas in others significant electron dominance is claimed (e.g., Isobe et al 2002;Comastri et al 2003;Kataoka et al 2003b). However, the results are dependent on the assumed electron energy spectrum and photon population characteristics.…”
Section: Introductionmentioning
confidence: 99%